Coordination of the Industrial-Ecological Economy in the Yangtze River Economic Belt, China - Yuan, Liang; Li, Renyue; He, Weijun; Wu, Xia; Kong, Yang; Degefu, Dagmawi Mulugeta; Ramsey, Thomas Stephen (Frontiers in Environmental Science, 2022)
The Yangtze River Economic Belt (YREB) is an important growth pole of China's economy, but it is also one of the most environmentally polluted basins in China. Maintaining the vitality of economic development while at the same time realizing the coordinated development of industry and ecosystems, is an important issue that needs in-depth discussion and research. This paper analyzes the degree of coordination regarding the industrial-ecological economy in the YREB, identifies important influencing factors and puts forward measures for improvement. First, an evaluation model of the industrial-ecological economy is constructed. Second, a model is constructed for the measurement of the coordination degree of the industrial economy and industrial ecology based on the Lotka-Volterra Model. Third, the relationship is assessed with respect to competition versus cooperation. Finally, the important factors affecting coordination are identified using a Neural Network Model. Four main conclusions can be drawn: (1) The comprehensive development of the industrial economy and industrial ecology in 11 provinces and cities in the YREB is generally trending upward. (2) The coordination level of the industrial-ecological economy in the midstream area is high. The provinces Jiangsu, Jiangxi, Sichuan, and Guizhou are in a coordinated state. (3) The midstream area has a more balanced industrial-ecological economy with significant symbiosis between the industrial economy and industrial ecology. Jiangsu, Jiangxi, Sichuan, and Guizhou Provinces show a symbiotic relationship; Shanghai City, Chongqing City, and Anhui Province show a partially symbiotic relationship; and Zhejiang, Hubei, Hunan, and Yunnan Provinces show a mutually inhibitory relationship. (4) The industrial ecosystem is the largest factor in the degree of coordination, and intensity of R&D investment, regional GDP per capita, and proportion of tertiary-industry added-value in GDP also have a great impact. Based on this analysis, this paper proposes measures for high-quality development of the industrial-ecological economy of the YREB with regard to balanced development of the industrial economy, transformation and upgrading of the surrounding environment, along with coordinated and integrated development.